Effects of Sea Surface Temperature on the Distribution of Short-finned Pilot Whales (Globicephala macrorhynchus) in the Western North Atlantic Ocean - Davis, Leah (2019)
Two species of pilot whales inhabit the western North Atlantic Ocean: short-finned pilot whales Globicephala macrorhynchus; and long-finned pilot whales G. melas. The two species are morphologically similar and difficult to differentiate in the field, so the National Marine Fisheries Service (NMFS) uses an algorithm based on sea surface temperature (SST) and water depth to determine species identity for stock assessment surveys and fishery bycatch records. NMFS assumes that short-finned pilot whales are found in waters warmer than 22°C, while long-finned pilot whales are typically found in waters colder than 25°C, with an overlap between the two species in waters from 22°C to 25°C. This area of overlap occurs primarily between latitudes 38°N and 40°N during summer months. I used short-finned pilot whale telemetry data to test this assumption regarding the thermal preferences of short-finned pilot whales. Only 7.4% of locations in the area of overlap occurred in waters below 22°C, and my analysis confirmed that sea surface temperature has a significant impact on habitat selection of short-finned pilot whales. These results will inform future pilot whale stock assessments in the western North Atlantic Ocean, assist in determining species identity of Atlantic pelagic longline fishery bycatch records, and provide a baseline for assessing potential range shifts in the western North Atlantic expected as a result of climate change.